Influence Satisfaction Work and Development Career to Performance BFI Finance Employees , Palopo City - Fadhil, Abd; Sampetan, Suparni; Sari, Nispa (Journal of Applied Business, Taxation and Economics Research, 2026)
This study aims to determine the influence of job satisfaction and career development on employee performance at BFI Finance in Palopo City. The approach used is a quantitative method with a questionnaire as the research instrument. The population in this study was 80 employees, with a sample selection technique based on certain criteria of 50 employees. fulfil criteria . The collected data was analyzed using statistical tests. SPSS version 27 was used to determine the relationship between variables. The results showed that job satisfaction and career development had a positive and significant effect on employee performance. This finding confirms that increased job satisfaction and the availability of good career development opportunities can be important factors in improving employee performance at BFI Finance, Palopo City.